CHANGES IN THE LEVEL OF TECHNICAL AND SCALE EFFICIENCY OF THE FOOD SECTOR ENTERPRISES IN POLAND IN THE YEARS 2006–2016 - Kozak, Sylwester; Kossowska, Karolina (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
This article empirically analyses evaluation of efficiency of Polish food producers. Technical and scale efficiency indices are measured using the non-parametric DEA method. The study is based on the annual financial reports of 51 sugar and confectionery producers operating in 2006–2016. The research revealed that technical efficiency of enterprises ranged from 82 to 93%, with the highest levels in periods of considerable increasing macroeconomic conditions in periods of 2006–2007 and 2013–2016. Most of companies characterised with the high efficiency and increasing return to scale. Throughout the entire period companies characterized with high scale efficiency at the interval of 87–93%.